Performance of existing definitions and tests for the diagnosis of invasive aspergillosis in critically ill, adult patients: A systematic review with qualitative evidence synthesis. Issue 1 (July 2020) - ,; Akova, M.; Alastruey-Izquierdo, A.; Arikan-Akdagli, S.; Azoulay, E.; Blot, S.; Cornely, O.A.; Lass-Flörl, C.; Koehler, P.; Cuenca-Estrella, M.; de Lange, D.W.; De Rosa, F.G.; et al.
Highlights: This systematic review will guide discussions within the FUNDICU project. Most available data pertained to IPA. The AspICU definition showed a promising diagnostic performance against histology. A better diagnostic performance of BALF GM than serum GM was observed. Suboptimal specificity was observed for BALF and serum (1, 3)-β-D -glucan. Abstract: Objectives: To summarize the available evidence on the diagnostic performance for invasive aspergillosis (IA) in non-hematological, non-solid organ transplantation critically ill patients of the following: ( i ) existing definitions of IA (developed either for classical immunocompromised populations or for non-immunocompromised critically ill patients); ( ii ) laboratory tests; ( iii ) radiology tests. Methods: A systematic review was performed by evaluating studies assessing the diagnostic performance for IA of a definition/s and/or laboratory/radiology test/s vs. a reference standard (histology) or a reference definition. Results: Sufficient data for evaluating the performance of existing definitions and laboratory tests for the diagnosis of IA in critically ill patients is available only for invasive pulmonary aspergillosis. Against histology/autopsy as reference, the AspICU definition showed a promising diagnostic performance but based on small samples and applicable only to patients with positive respiratory cultures. Studies on laboratory tests consistently indicated a better diagnostic performance of bronchoalveolar lavage fluid (BALF) galactomannan (GM) than serum GM, and a suboptimal specificity of BALF and serum (1, 3)-β-D -glucan. Conclusions: Evidence stemming from this systematic review will guide the discussion for defining invasive aspergillosis within the FUNDICU project. The project aims to develop a standard set of definitions for invasive fungal diseases in critically ill, adult patients.